-3x^2 = -12
x^2 = 4
x = ±2
thanks and what about this one ?
Simplify the expression
I'm getting confused because of the negative exponent
anything^0 = 1, so we just have
(3x^-1y^2)^3 = 27 x^-3 y^6 = 27y^6/x^3
negative exponents indicate a swap between numerator and denominator
x^-3 = 1/x^3
1/x^-3 = x^3
recall that x^a/x^b = x^(a-b)
Answer this Question
precal - Solve for y: (y-(10/y))^2+6(y-(10/y))-27=0
precal - solve for x: (x^2-2x)^2 -11(x^2-2x)+24
PreCal - Solve The Inequality 0 < -9x/x-x^2
precal - solve by subsituting 5x+4y=7 x-3y=9
precal 2 - solve the equation 4cos^2x-1=0
precal - How do you solve: sin[arccos(-2/7)] ?
PreCal - Solve Using Log Properties: 1/4 = 8^3x+5
Precal - Solve the exponential equation algebraically 5^(-t/2) = 0.20
PreCal - I'm suppose to solve log(3)-27=x I get 3^x=-27 I can't go any father ...
precal 2 - use the law of cosines to solve the triangle a=55, c=72, b=25